Warming and elevated CO2 interactively affect the photosynthetic carbon of maize plant retained in major farming soils. Issue 4 (21st March 2021) - Fang, Rui; Li, Yansheng; Yu, Zhenhua; Xie, Zhihuang; Wang, Guanghua; Liu, Xiaobing; Liu, Junjie; Herbert, Stephen J; Jin, Jian
ABSTRACT: Warming and elevated CO2 (eCO2 ) may influence the input of photosynthetic carbon (C) into soils and subsequent soil C storage. The biochemical properties vary among soils, which likely act different roles in the fate of photosynthetic C and soil C sequestration in response to warming and eCO2 . However, the interactive effects of climate change and soil types on the photosynthetic C retained in soil and relevant mechanisms are poorly understood. We performed a pot experiment in open-top chambers to examine the effects of eCO2 (550 ppm) combined with elevated temperature (eT, 2 °C higher than the air temperature) on the retention of plant-C of maize ( Zea mays L.) grown in Phaeozem, Fluvisol, Kastanozem and Acrisol with 13 CO2 labeling at the silking stage. The proportion of 13 C to the total fixed 13 C increased by 44.6%, 96.1% and 41.9% in Phaeozem under eT, eCO2 and eT plus eCO2 treatments compared with control, while decreased in other three soils in response to either eCO2, eT or eT plus eCO2 . The effect of climate change on fresh C input in maize cropping soils depended on soil type, and soil net C losses may occur in the Fluvisol, Kastanozem and Acrisol under climate change. Abbreviations : eCO2 : elevated CO2, 550ppm; eT: warming; aCO2 : ambient CO2, 400ppm; aT: ambient temperature; OTC: open-top chamber; DOC: dissolved organic carbon; SOC: soil organic carbon; C: carbon; S: soil; T: temperature.